Disinformation and memetics: replication and mutation of antivaccine arguments in informative content - Sánchez-Olmos, Cande; Rodríguez-Ferrándiz, Raúl; Hidalgo Marí, Tatiana (Cuadernos de Documentación Multimedia, 2024)
Disinformation about vaccination is as old as the origin of the vaccines that emerged at the end of the 18th century, its reach is transnational and it has posed a challenge not only to the information landscape, but also to public health, especially during the Covid-19 pandemic. Although the fake news spread by anti-vaccine advocates was disproved during prior epidemics, the old anti-vaccine ideas were resurrected in a hypermedia digital ecosystem that multiplied the replication of disinformation, especially during the pandemic. This paper aims to determine whether there are memetic characteristics in the disinformation disseminated by contemporary anti-vaccine advocates in a sample of disinformation content from both the nineteenth century and the present day. First, the origin of the anti-vaccine movement is documented. Next, formats and means of dissemination of disinformation from its origins to Covid-19 are described. Finally, anti-vaccine arguments from the 19th century are extracted and compared to current ones by applying Dawkins' memetic theory. This study finds that current anti-vaccine ideas contain memetic characteristics of 19th century arguments that have been replicated in fake news, hoaxes, social networks and billboards, resurrecting a disinformation that has eroded the credibility of vaccination. Specifically, the anti-vaccine argument is long-lived, because it persists with similar ideas today, particularly fruitful due to the capacity of replication offered by interactive digital media, but less reliable, because anti-vaccine ideas have mutated adapting to the current social context.
Keywords: memetics; fake news; disinformation; anti-vaccine; Covid-19